Service quality and customer satisfaction: a study of listed banks at colombo stock exchange (cse) in sri lanka - Kaluarachchi, I. P.; Gamlath, G.R.M. (university of Jaffna, 2014)
Banking and finance industry has been rapidly growing over the past decade resulting in an intense competition which has allowed the customers to use multiple banks and switching from one bank to another seeking better opportunity. Most of the banking product developments are easy to be duplicated and when banks provide nearly identical services the main differentiator is the level of service quality and how the customers perceive it. This study attempts to analyze the relationship between the service quality and the level of customer satisfaction and to analyze the influence of each separate service quality parameter on the customer satisfaction. Research was conducted by using a sample of 250 randomly selected customers of CSE listed banking firms located in a slightly remote area. This study measures the service quality in terms of tangibility, reliability, responsiveness, assurance and empathy. Findings revealed that the service quality has a significant influence on the customer satisfaction. Assurance was identified to have the strongest influence on customer satisfaction.
Keywords: Service quality; Customer satisfaction; Banking industry